(untitled) (AYUSHDHARA, 2024)
Gridhrasi is one amongst the Vatavyadhi and is characterized by pain in Sphik region radiating to Kati, Prushta, Uru, Janu Jangha and Pada. It can be grossly correlated to sciatica due to the resemblance in signs and symptoms. Sciatica refers to the condition characterized by pain that radiates along the path of the sciatic nerve, from the lower back to the lower limbs. It is usually caused by a herniated disc and is characterized by protrusion or extrusion of the nucleus pulposus through a rent in the annulus fibrosus, which causes compression of the exiting nerve root leading to the excruciating pain in the lower back radiating to one or both the lower limbs. Its peak incidence is seen in the fourth decade, with the lifetime incidence of 10 – 40%. In this case a female patient aged 43 years suffering from pain in the lower back radiating to right lower limb was effectively managed with Kulatha Pinda Sweda, Rasna Erandadi Kashaya Basti and Agnikarma. The patient reported significant improvement in pain, heaviness, tingling sensation and range of movement.